COMMUNICATION BETWEEN SPOUSES FOR GENDER EQUALITY IN CONTRACEPTION USE - Puri Kusuma Dwi Putri (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
The use of contraceptives is still a gender bias for family based health development. Why is always woman who have been the subject of family planning? The use of contraceptives is not as the nature of women. The family has not yet become a place where gender equality begins. It might due to the values, norms, and culture inherited from parents, that women can willingly accept every word of the husband. The role of women in the success of male family planning is also spearheading the development of national development originated from a family as the women get a lot of information about family planning. Mindset of the women also need to be changed with the women as the subject of family planning, there is also a fear of her husband having an affair as they refuse the vasectomy. In another side, there is also opinion that men is also important in family planning as the side effects of the  use of contraceptives  are  more  widely  experienced by  women.Redefining the  meaning of the  family can mean  the  participation  of  men  in  the  use  of  contraceptives,  such  as  those  conducted  by  Ismail  Hussein, PriyoUtomo,  Suku  Using,  and  the  general  public  who  participated  in  the  World  Vasectomy  Day.  Speaking  of family  planning  and  Knowledge  of  reproductive  health  in  the  family  is  not  as  taboo  and  sensitive  talks.  Thus, family communication is a forum for gender equality in the use contraceptives which aims to improve the welfare of family. Keywords: contraceptives, women, family, gender equality, participation